Contributory Factors related to the Tensile Strength of Hot Mix Asphalt Concrete - Oleiwi, Mina M.; Albayati, Amjad K. (Engineering, Technology & Applied Science Research, 2024)
Tensile strength is a critical property of Hot Mix Asphalt (HMA) pavements and is closely related to distresses such as fatigue cracking. This study aims to evaluate methods for assessing fatigue cracking in Asphalt Concrete (AC) mixes. In order to achieve optimum density at different binder contents, the mixes were compressed using a gyratory compactor. Tensile strength was assessed using the Indirect Tensile (IDT) and Semi-Circular Bend (SCB) tests. The results showed that the tensile strength measured by the SCB test was consistently higher than that measured by the IDT test at 25 °C. In addition, the SCB test showed a stronger correlation between increasing binder content and tensile strength. For binder contents ranging from 4.2% to 5.2%, the IDT test results increased from 541% to 678.7%, while the SCB test results increased from 630.3% to 743.7%. These results suggest that the SCB test provides a more accurate representation of the tensile strength of AC mixes than the IDT test.